THE QUALITY OF LIFE AND ITS DETERMINANTS AMONG ELDERLY WHO LIVING WITH CHRONIC NON-COMMUNICABLE DISEASE - Harisa, Akbar; Asrina, Asrina; Abdullah, Lilian Arifka Juli; Soleha, Dinda; Yodang, Yodang (Jurnal Perawat Indonesia, 2022)
Background: Chronic diseases include non-communicable diseases have been a health burden globally particularly for older people.  Since the ageing population is being increased during few decades. The incidence of non-communicable diseases among older people also increased, and continues to rise as alongside the growth of aging. There many studies identified that chronic disease affect the health-related quality of life among older people. Purposes: This study aims to identify the quality of life and its determinant among older people who living with chronic non-communicable disease.  Methods: This study applied a cross section survey design. The study participants are elderly who visit primary health care, and older people who have a chronic disease. The study conducted in two primary health care facilities, in Makassar. Results: there are 41 participants who involve in this study. Predominantly participants were late older in group of age (48.8%), female (75.6%), have secondary level in education (41.5%), currently employ (85.4%), divorce status (58.5), have hypertension history range from 1-5 years (73.2%), and have complications (58.5%). The complication of disease shows significant impact on the quality of life (p<0.05, p=0.022). Since the sample size was small this may affect the study results. Conducting research in large sample and add some characteristics are needed in order to improve the evidence.   Keywords: Quality of life, Elder people, Non communicable disease